1997
DOI: 10.2514/2.3293
|View full text |Cite
|
Sign up to set email alerts
|

Galileo Probe Heat Shield Ablation Experiment

Abstract: The Galileo Probe deceleration module contained an experiment that measured the surface recession of the forebody heat shield during the hypersonic entry into the Jovian atmosphere. A detailed description of the experiment, reduction of the recession data, reconstruction of the heat-shield shape history, and comparisons with pre ight predictions are presented. Sensor performance was compromised by an extraneous signal during the rst half of the hypersonic entry, but data quality was reasonably good for the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…Measurements of a test vehicle with a low-drag (␦ ϭ 0.06) carbon nosecone entering the Earth's atmosphere at 6 km͞sec showed an ablative loss of Ϸ0.1 kg, for a mass-loss to energy-loss ratio of 0.14 kg͞GJ (10). A similar ratio of 0.25 kg͞GJ was measured for the Galileo probe, which entered Jupiter's atmosphere at 47 km͞sec and was brought to rest by a carbon ablation shield designed for high drag (11). In our case, a 4 ton͞m 2 vehicle losing 77 GJ͞m 2 would suffer an ablation loss of 20 kg͞m 2 , if the loss rate were 0.25 kg͞GJ.…”
Section: From the Earth To L1mentioning
confidence: 65%
“…Measurements of a test vehicle with a low-drag (␦ ϭ 0.06) carbon nosecone entering the Earth's atmosphere at 6 km͞sec showed an ablative loss of Ϸ0.1 kg, for a mass-loss to energy-loss ratio of 0.14 kg͞GJ (10). A similar ratio of 0.25 kg͞GJ was measured for the Galileo probe, which entered Jupiter's atmosphere at 47 km͞sec and was brought to rest by a carbon ablation shield designed for high drag (11). In our case, a 4 ton͞m 2 vehicle losing 77 GJ͞m 2 would suffer an ablation loss of 20 kg͞m 2 , if the loss rate were 0.25 kg͞GJ.…”
Section: From the Earth To L1mentioning
confidence: 65%
“…1,2 As a result, massive ablation occurred that resulted in a substantial reduction of the heat shield mass. 1 The flight data revealed that there was a significant discrepancy of the final recession profile from that given by the preflight prediction. Indeed, the amount of recession occurred at the stagnation region deduced from the flight data was almost three-fourths and that at the frustum region was almost double when compared with those given by the preflight prediction.…”
Section: Introductionmentioning
confidence: 82%
“…Forebody distributions of radiative heating at different trajectory locations [58]. The flight data have been analysed [70,71] and the entry trajectory, as well as the atmospheric properties have been determined. They are all reported in Table 6.…”
Section: Survey and Computational Matrixmentioning
confidence: 99%
“…Galileo probe was equipped with ablation detector sensors (ARAD) for collecting flight data during entry. The in-flight experiments have been well detailed by Milos [70]. Ten ablation sensors were included in the TPS, at 6 different locations, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation